A model for renewable energy-based product innovation based on TRIZ methodology, exergy analysis and knowledge management: Case study. (November 2022) - Alvarez, José C.; Hatakeyama, Kazuo; Carvalho, Monica; Marçal, Roberto C.; Inche, Jorge; de Melo, Norma
Abstract: Eco-innovation is the innovation of products that focuses on the use of renewable energy and meets specific environmental requirements, and is essential for energy conservation and environmental protection. There are recommendations and strategies available for general product development, but there are limited studies when focusing on renewable energy products. A proposal for eco-innovation in renewable energy is developed based on exergy analysis, TRIZ methodology, and knowledge management. The model is demonstrated with a specific case study. This study contributes to the analysis and development of products with renewable energy that help mitigate climate change, consistent with the change in the energy matrix. Furthermore, this study is a transdisciplinary effort that integrates concepts from different topics to achieve a comprehensive model.